Approaching a New Normal: Lessons Learned Transitioning Family Education Programming to a Virtual Environment. Issue 1 (January 2023) - Corvin, Jaime; Nabours, Bradlie; Bularca, Sinziana; Haile, Amy
The COVID-19 pandemic is highlighting deep-rooted health inequities. While the virus itself does not discriminate, gaps in access to services and disparities in health outcomes are prevalent. Concerns over worsening mental health outcomes and increases in family violence exist. Thus, service organizations have faced an unprecedented call to rethink services, with many transitioning to virtual programming to ensure the needs of their clients can be met. This brief highlights lessons learned as one organization pivoted to meet critical client needs during the COVID-19 pandemic. Evidence suggests atypically high engagement and retention in family education and family violence reduction programming under Safer at Home orders when compared with pre-COVID engagement. Findings suggest key tenants for program success are tied to strong programming, staff engagement, and participation retention and satisfaction. Program adaptations create opportunities for increasing service equity, improving engagement and satisfaction, and improving family and mental health outcomes by maintaining connections, while providing a model for delivering services to reduce child maltreatment during times of social isolation and increased hardship.